2008
DOI: 10.3892/mmr_00000016
|View full text |Cite
|
Sign up to set email alerts
|

The granulocyte/lymphocyte ratio as an independent predictor of tumour growth, metastasis and progression: Its clinical applications

Abstract: Abstract. Several investigators have suggested that the granulocyte/lymphocyte (G/L) ratio is a good indicator for the evaluation of the condition of a tumour-bearing host, although its prognotic significance is unclear. To further investigate the clinical applications of the G/L ratio, we injected 1x10 5 and 1x106 Lewis lung carcinoma cells (3LLc) into the feet of 4-week-old C57BL/6 mice separated into groups A, B, C and D (1x10 5 cells) and E, F, G and H (1x10 6 cells). For the observation of tumour metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 11 publications
1
19
0
3
Order By: Relevance
“…This increase continues with the progression of the disease, reaching a state of acute neutrophilia with neutrophils making~90 % of all circulating white blood cells [32]. Similar increase in circulating neutrophil numbers was seen in other mouse models of cancer including Lewis lung carcinoma [163] as well as in spontaneous mouse models such as the MMTV-PyMT and MMTVWnt1 transgenic mice [32], where tumor initiation is driven by a transgene, rather than an engrafted tumor. In a rat model of 13762NF mammary adenocarcinoma cells, the number of circulating neutrophils did not increase in poorly metastatic cells, whereas the number rose 50-fold in rats bearing a highly metastatic clone [164].…”
Section: Regulation Of Neutrophil Mobilization Recruitment and Activmentioning
confidence: 66%
See 1 more Smart Citation
“…This increase continues with the progression of the disease, reaching a state of acute neutrophilia with neutrophils making~90 % of all circulating white blood cells [32]. Similar increase in circulating neutrophil numbers was seen in other mouse models of cancer including Lewis lung carcinoma [163] as well as in spontaneous mouse models such as the MMTV-PyMT and MMTVWnt1 transgenic mice [32], where tumor initiation is driven by a transgene, rather than an engrafted tumor. In a rat model of 13762NF mammary adenocarcinoma cells, the number of circulating neutrophils did not increase in poorly metastatic cells, whereas the number rose 50-fold in rats bearing a highly metastatic clone [164].…”
Section: Regulation Of Neutrophil Mobilization Recruitment and Activmentioning
confidence: 66%
“…From then on, a large number of clinical studies have been performed to understand the neutrophil-cancer relationship. Clinical data have often related elevated circulating neutrophil counts or elevated neutrophil-to-lymphocyte ratios (NLRs) as a predictive parameter for poor outcome and formation of distant metastasis in patients with epithelial malignancies [367], including lung [368,170], gastric [159,163,369], renal cell carcinoma [370], ovarian [141], hepatic [143,148,371], pancreatic [138], colon cancer [145,372], and colorectal carcinoma [152] (Table 3). However, Caruso et al [200] observed that when analyzing the amount of tumor-infiltrated neutrophils in advanced gastric carcinoma, in female but not male, patients with higher TANs had a favorable prognosis.…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 99%
“…Studies on gastrointestinal cancer have supported the hypothesis that the N/L ratio is significantly associated with overall survival (OS) in patients with colorectal cancer (7,8). In a previous study, we found that the peripheral blood N/L ratio is associated with tumor size and is an independent indicator of survival in patients with rectal carcinoma (9). The independent prognostic role of the peripheral blood N/L ratio for malignant bone metastasis at diagnosis remains to be confirmed.…”
Section: Introductionmentioning
confidence: 88%
“…In a previous study, a positive linear correlation was observed between tumor weight and the N/L ratio within an animal model (14), and an increased N/L ratio was associated with poor prognosis because elevated levels of granulocytes promote tumor growth by antagonizing tumor-suppressing lymphocytes. Those results indicate that opposing fluctuations in the neutrophil and lymphocyte counts may be associated with tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies on gastrointestinal cancer have supported this theory. We have previously reported that the N/L ratio was significantly associated with increased tumor stage and overall survival of patients with gastric and rectal cancer (14,15). One theory is that the high N/L ratio reflects the poor status of the immune system against cancer and/or the progression of cancer, but no previous studies have demonstrated that the N/L ratio may serve as an independent indicator of chemotherapy effect for patients with unresectable or recurrent gastric cancer.…”
Section: Introductionmentioning
confidence: 99%